A regio- and stereoselective Heck–Matsuda process for construction of γ-aryl allylsulfonyl fluorides. Issue 30 (4th July 2022) - Qin, Hao-Yong; Gui, Houying; Zhang, Zai-Wei; Shu, Tao; Qin, Hua-Li
Abstract : A Heck–Matsuda reaction of aryl diazoniums with allylsulfonyl fluorides for the construction of γ-aryl allylsulfonyl fluorides was developed. Abstract : A highly efficient regio- and stereoselective Heck–Matsuda method was developed employing aryl diazoniums and allylsulfonyl fluorides for the construction of a class of novel γ-aryl allylsulfonyl fluorides in the presence of Pd(OAc)2 and PPh3 . The method features excellent regio- and stereoselectivity (up to 100% E -selectivity), broad substrate scope and mild reaction conditions. Further application of γ-aryl allylsulfonyl fluoride in SuFEx reactions was achieved to provide their corresponding sulfonates and sulfonamides in excellent yields.